Impact of simulated ski-specific shocks on force, time, and knee angle parameters: A pilot study - Raschner, C.; Mutschlechner, L. (Science and Skiing VII, 2018)
Alpine ski racing is a high-speed sport characterized by complex technical and physical demands. Extreme external forces due to an unpredictable environment often occur during competitions and training. These circumstances lead to an increased risk of traumatic and overuse injuries (Jordan et al., 2017; Spörri et al., 2017). Hence, regardless of age and gender, ski racers require high physical fitness to cope with the rigors of racing and training that are placed upon the musculoskeletal system. In addition, strength parameters (e.g., maximal strength, power, strength endurance, and stabilization-oriented strength) are of utmost importance (Raschner & Müller, 2001; Patterson et al., 2009; Turnbull et al., 2009). Biomechanical studies have demonstrated the importance of eccentric muscle actions in ski-racing situations (Berg et al., 1995; Kröll et al., 2015). Additionally, the stretch-shortening cycle (SSC) plays an important role (Frick et al., 1997; Kröll et al., 2015). When skiing through bumpy sections or when a ski suddenly hits a hole or rut, racers are exposed to short, unexpected eccentric or concentric shocks. For example, athletes must navigate along the bumpy traverse in the downhill race in Kitzbühel, where, in 2015, an unpredicted hole in the piste together with bad ground-light led to unforeseen high forces that resulted in crashes with severe injuries to three top athletes. It is difficult to simulate these extreme ski-specific loads and shocks during strength training. Although elite athletes can improve the quality of their strength training using ski-specific exercises (Raschner et al., 1997; Müller et al., 2000), mechatronic devices are seldom implemented in strength-training programs. Therefore, the aim of this study was twofold: the first aim was to identify an adequate way of generating ski-specific shocks using a mechatronic-driven training device, and the second was to compare different shocks in terms of force, time, and knee angle parameters.